Recent development of catalysts for removal of volatile organic compounds in flue gas by combustion: a review - Tomatis, Marco; Xu, Hong-Hui; He, Jun; Zhang, Xiao-Dong (Hindawi Publishing Corporation, 2016)
Volatile organic compounds (VOCs) emitted from anthropogenic sources pose direct and indirect hazards to both atmospheric environment and human health due to their contribution to the formation of photochemical smog and potential toxicity including carcinogenicity. Therefore, to abate VOCs emission, the catalytic oxidation process has been extensively studied in laboratories and widely applied in various industries. This report is mainly focused on the benzene, toluene, ethylbenzene, and xylene (BTEX) with additional discussion about chlorinated VOCs. This review covers the recent developments in catalytic combustion of VOCs over noble metal catalysts, nonnoble metal catalysts, perovskite catalysts, spinel catalysts, and dual functional adsorbent-catalysts. In addition, the effects of supports, coke formation, and water effects have also been discussed. To develop efficient and cost-effective catalysts for VOCs removal, further research in catalytic oxidation might need to be carried out to strengthen the understanding of catalytic mechanisms involved.